OPTIMALISASI MANAJEMEN SEBAGAI UPAYA PENINGKATAN EFEKTIVITAS DAN KEBERLANJUTAN OPERASIONAL TERAPI BHAKTI LUHUR - Purba, Tio Pratama Putra; Nur Afifah; Lisa Vania; Alian Maura; Darul Agnil Satrio; Ruwitri Agustina (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
The community service program at Therapy Bhakti Luhur Pontianak was implemented with the aim of improving the business management capacity and independence of children with disabilities. The background to this activity was the limited human resources in managing the marketing of the orphanage's products, such as batik, bead bracelets, and rosaries, as well as the children's low self-management skills. The implementation method included the development of a marketing management education website, self-management training with a participatory approach, and holding a Talk Show and Beads Workshop involving the community. The results of the activity showed an increase in the competence of the management in digital marketing, product packaging, and social media optimization. On the other hand, the children showed development in aspects of self-regulation, collaboration skills, and emotional expression. This program is aligned with Sustainable Development Goals (SDG) 10, Reduced Inequalities, through efforts to eliminate discrimination and strengthen social inclusion. Overall, this activity makes a significant contribution to the empowerment of the orphanage and children with disabilities, and has the potential to be replicated in similar institutions.